The Stigma Of Being Hiv Patients In North Central Nigeria: Socio-Economic And Cultural Factors - Bala, Nalah Augustine (2021)
HIV stigma constitutes a discriminatory and dehumanizing attitude experienced by HIV patients, affecting the social, physical, mental, and psychological well-being. This study aims to provide a detailed descriptive analysis of the influence of socio-demographic variables like socio-cultural, socioeconomic, education, religion, and gender inequality as determinants of the stigma of being HIV patients. The population centered on diagnosed and admitted outpatients from selected Federal Medical Centers (FMC) Keffi, General Hospitals Akwanga (GHA), and Dalhatu Araf Specialists Hospital (DASH) Lafia, all designated for the HIV care across Nasarawa State, North Central Nigeria. The sample comprises male and female aged 18 consented to be stigmatized for being HIV patients. In this qualitative phenomenological based study, a non-randomize technique using a purposive sampling technique to select 20 samples from hospitals designated to handling HIV cases in Nasarawa State, North Central Nigeria. Data collection utilized an in-depth face to face interview using an audio recorder and field notes. A Computer-Assisted Qualitative Data Analysis Software (CAQDAS) using ATLAS.ti8 to analyze the unstructured data collected through audiotape, note-taking, and all other field data. The ATLAS.ti8 analyzes and code interview transcripts by systematically converting, transcribing, and presenting data into a textual form using thematic analysis. The coded data were presented graphically through thematic network analysis to visualize the themes, sub-themes, and quotations by designing the psychosocial model of HIV stigma from the findings.